2021
DOI: 10.1159/000516560
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection Associated with Autism Spectrum Disorder: A Case Report

Abstract: <b><i>Introduction:</i></b> The aim of this case was to investigate the association of the Zika virus infection in utero with the autism spectrum disorder (ASD) as clinical outcome that presented no congenital anomalies. <b><i>Methods:</i></b> ASD was diagnosed in the second year of life by different child neurologists and confirmed by DSM-5 and ASQ. After that, an extensive clinical, epidemiological, and genetic evaluations were performed, with main known ASD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to a database of imaging studies, cranial characteristics of children with microcephaly were described, including a substantial increase in ventricle volumes, cortical and subcortical atrophy, cerebellar hypoplasia and abnormalities in the white matter, corpus callosum, basal ganglia, and trunk, as well as calcifications in different brain regions (Schuler‐Faccini et al, 2022; Wu et al, 2018). Moreover, diagnosis of autism spectrum disorders (ASD) in childhood were recently correlated with ZIKV infection during pregnancy (Santi et al, 2021; Vianna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to a database of imaging studies, cranial characteristics of children with microcephaly were described, including a substantial increase in ventricle volumes, cortical and subcortical atrophy, cerebellar hypoplasia and abnormalities in the white matter, corpus callosum, basal ganglia, and trunk, as well as calcifications in different brain regions (Schuler‐Faccini et al, 2022; Wu et al, 2018). Moreover, diagnosis of autism spectrum disorders (ASD) in childhood were recently correlated with ZIKV infection during pregnancy (Santi et al, 2021; Vianna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, organoid models have been successfully applied to study events of neural precursor cell dysfunction occurring in the early stages of brain development, including precursor cell abnormalities of Zika virus infection and its resulting microcephaly‐related phenotypes, 59,60 which were the first developmental disorders to be studied in organoids 7 . The use of organoids successfully revealed that the Zika virus disrupts the apical junctions of radial glial cells (RGCs) through the protein NS2A, 61 causing RGCs to proliferate less, produce fewer neurons, and produce apoptosis, 9,62 leading to disruption of ventricular zone structures and RGC scaffolds and tissue structural disruption, 63 ultimately producing a microcephalic phenotype 64,65 .…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Recently a cohort analyzed in an in utero exposed children has presented 2.1% of individuals diagnosed with autism ( Nielsen-Saines et al, 2019 ). Although the limitations of this cited report cannot ensure that ZIKV infection is responsible for the disease, our group reported a child diagnosed with autism presented the exposure to ZIKV in utero as the only abnormality among all known molecular and genetic causes for autism ( Santi et al, 2021 ). Amyotrophic lateral sclerosis (ALS) and AD have presented an expressive number of genes in the neurodegenerative diseases group, followed by Parkinson’s disease (PD) and multiple sclerosis ( Figure 6B ).…”
Section: Mechanisms: Lessons From Experimental Studiesmentioning
confidence: 97%